Structural behavior of Lightweight and High strength Layered Hollow Core Slabs (Fracture and Structural Integrity, 2022)
A new technique of Layered Hollow Core Slab (LHCS) has been used to obtain a slab with an optimum weight-to-strength ratio. Specimens with a 90 mm top layer of High Strength Concrete (HSC) and a 90 mm bottom layer of Lightweight Aggregate Concrete (LWAC) were examined. Nine full-scale slabs with dimensions of 1600* 450* 180 mm were tested under a 4-point loading test. The %core, a/d, RFT ratio, and connection method were the different studied parameters. A push-out test was conducted on triplet specimens to study the bond strength at the interface between HSC jacket and LWAC cubes using bond agent material or shear dowels, or without treatment, to determine which method of them is suitable for connecting the two layers of the tested slabs. Load, deflection, ductility, strain, crack pattern, and mode of failure were studied. The results indicate that ultimate strength is enhanced with decreasing a/d and %core and with an increasing RFT ratio of the LHCS specimens. Using shear dowels ensures an efficient bond between the two layers of the tested slabs. ANSYS program used for modelling the slab. The numerical study accepted the experimental data with a variation of less than 10% for all slabs.
Keywords: Hollow core slab; Layered slab; Lightweight aggregate concrete; High strength concrete